STUDI TENTANG PENAMBAHAN AIR DI BUMI OLEH ASTEROID BERPOTENSI BAHAYA - Latifatul Munawaroh, Alisa
To this day, it is known that Earth is the only planet in the Solar System that has liquid water and supports life to evolve. The unknown origin of water on Earth and the increasing need for fresh water raise a question: "Is water on Earth still likely to increase in this era?". Various studies have shown that there could be three sources of water on Earth: Earth rocks that trapped minerals at the beginning of the formation of the solar system, comets and asteroids. In this nal project, the research is focused on one of the suspected water contributors, asteroid. The method used here is by examining asteroid data including PHA which might have more potential to enter the Earth. The selected asteroids were then examined for the appropriate parameters: E MOID, diameter, magnitude, taxonomic type, and density. The data used are NEO, PHO, NEA, and PHA. From the collected data, only Asteroid 285263 1998 QE2 was followed up for the calculation of probability of carrying water when it reaches the earth's surface. It is 2.750 meters in diameter and if it hits Earth, can contribute as much water as (1,07±2,675) x 10^11 kg under current atmospheric conditions. It takes at least 10^10 asteroids to donate water to equal the mass of water in Earth's oceans. Therefore, the addition of water to Earth by asteroids constitutes a very small percentage or practically unexpected.